2019
DOI: 10.1111/jvs.12695
|View full text |Cite
|
Sign up to set email alerts
|

Floating ability, shoot length and abundance facilitate hydrochorous dispersal of moss and liverwort fragments

Abstract: Question Vegetative diaspores are pivotal to the ability of bryophytes to colonize new areas, but life‐history traits and other factors facilitating vegetative hydrochorous dispersal are largely unknown. Here, we ask whether hydrochorous dispersal of vegetative bryophyte fragments can be predicted by specific traits in addition to discharge and abundance of species in the vegetation. Location The Twentekanaal, a navigation canal in the Netherlands. Methods Over a one‐year period, viable bryophyte fragments dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Nurminen et al (2003) has previously shown bryophytes to be part of the diet of Rudd, but these authors did not establish viability of egested fragments. Our study thus presents the first evidence that ichthyochory may significantly contribute to vegetative dispersal of several aquatic and riparian moss species, confirming earlier assumptions by Glime (2017) and complementing dispersal by hydrochory (Boedeltje et al, 2019). Given the small size (0.2-0.4 mm) of egested moss fragments, and that they were found throughout the year, we hypothesize that bryophytes were ingested when fish were foraging in the soft sediment (including the propagule bank with moss fragments) or feeding on invertebrates living in moss cushions on submerged stones in the stream (cf.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nurminen et al (2003) has previously shown bryophytes to be part of the diet of Rudd, but these authors did not establish viability of egested fragments. Our study thus presents the first evidence that ichthyochory may significantly contribute to vegetative dispersal of several aquatic and riparian moss species, confirming earlier assumptions by Glime (2017) and complementing dispersal by hydrochory (Boedeltje et al, 2019). Given the small size (0.2-0.4 mm) of egested moss fragments, and that they were found throughout the year, we hypothesize that bryophytes were ingested when fish were foraging in the soft sediment (including the propagule bank with moss fragments) or feeding on invertebrates living in moss cushions on submerged stones in the stream (cf.…”
Section: Discussionsupporting
confidence: 90%
“…Wet filter papers in petri dishes also were used as regeneration substrate for vegetative parts of bryophytes (Boedeltje et al, 2019; Figure S3). The closed dishes were exposed to natural day light conditions (without direct sunlight) in an unheated room (mean temperature 18 • C) and watered with tap water when necessary.…”
Section: Sorting and Testing The Viability Of Plant Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies on hydrochory are mainly performed in natural water bodies, such as rivers, streams, lakes, or in non‐natural agricultural ditches (Andersson et al, 2000; de Jager et al, 2019; Riis & Sand‐Jensen, 2006; Soomers et al, 2010; Su et al, 2019). These studies have found that the dispersal characteristics of hydrochorous propagules are determined by extrinsic and intrinsic factors (Chambert & James, 2009; Nilsson et al, 2010), such as hydrologic regimes, channel morphology, instream obstacles, flow velocity (Bång et al, 2007; Merritt & Wohl, 2002; Riis & Sand‐Jensen, 2006), meteorological conditions (Sarneel et al, 2014; Soomers et al, 2010; Su et al, 2019) and propagule buoyancy (Boedeltje et al, 2004, 2019; Nilsson et al, 2010). The relative importance of those factors varies among different types of water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Wind, however, usually becomes the dominant factor in lentic water bodies (Sarneel et al, 2014; Soomers et al, 2010) since the wind can blow through longer distances without meeting instream obstacles and thereby becomes stronger (Nilsson et al, 2002). Propagule buoyancy is an important intrinsic factor affecting dispersal distance (Boedeltje et al, 2004, 2019; Riis & Sand‐Jensen, 2006).…”
Section: Introductionmentioning
confidence: 99%